2021
DOI: 10.21203/rs.3.rs-1107846/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNA-141-3p Attenuates Oxidative Stress-induced Hepatic Ischemia Reperfusion Injury via Keap1/Nrf2 Pathway

Abstract: Hepatic ischemia reperfusion injury (IRI) is a major factor affecting the prognosis of liver transplantation through a series of severe cell death and inflammatory responses. MicroRNA-141-3p (miR-141-3p) has been reported to be associated with hepatic steatosis and other liver diseases. However, the potential role of miR-141-3p in hepatic IRI is currently unknown. In the present study, we found that miR-141-3p levels were negatively correlated with alanine aminotransferase (ALT)/aspartate aminotransferase (AST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Only two miRNAs (miR-141-3p and miR-192-5p) have been identified in humans. Li et al [ 88 ] collected serum samples from 27 Liver transplantation patients at different time points (pre-operatively, 4 h after reperfusion, and on postoperative days 1, 2, and 3) and measured the expression of miR-141-3p, ALT, and AST. They found that 4 h after perfusion, miR-141-3p was lower than pre-operation and then gradually increased over time, which manifested a negative correlation with ALT/AST levels[ 87 ].…”
Section: Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two miRNAs (miR-141-3p and miR-192-5p) have been identified in humans. Li et al [ 88 ] collected serum samples from 27 Liver transplantation patients at different time points (pre-operatively, 4 h after reperfusion, and on postoperative days 1, 2, and 3) and measured the expression of miR-141-3p, ALT, and AST. They found that 4 h after perfusion, miR-141-3p was lower than pre-operation and then gradually increased over time, which manifested a negative correlation with ALT/AST levels[ 87 ].…”
Section: Mirnasmentioning
confidence: 99%
“…Roy and his colleagues detected miR-192-5p expression in the liver tissues and sera of patients with acute liver injury. The results shown that miR-192-5p decreased in liver samples, but elevated in serum levels from patients with acute hepatic injury; further investigation revealed that miR-192-5p concentrations in serum were positively correlated with AST, ALT, and miR-122 Levels, which might represent a hepatocyte-specific serum biomarker[ 88 ].…”
Section: Mirnasmentioning
confidence: 99%